Intra-household resource allocation: Do parents educe or reinforce child cognitive ability gaps? - Paul Frijters; David W. Johnston; Manisha Shah; Michael A. Shields (Institute for the Study of Labor (IZA), 2010)
Do parents invest more or less in their high ability children? We provide new evidence on this question by comparing observed ability differences and observed investment differences between siblings in the NLSY. To overcome endogeneity issues we use sibling differences in handedness as an instrument for cognitive ability differences, since handedness is a strong determinant of cognitive ability. We find that parents invest more in high ability children, with a one standard deviation increase in child cognitive ability increasing parental investments by approximately one-third of a standard deviation. Consequently, differences in child cognitive ability are enhanced by differential parental investments. This finding has important implications for education policy.
Keywords: D13; J1; 330; children; cognitive ability; parental investment; handedness; Kinder; Kognitive Fähigkeiten; Eltern; Bildungsinvestition; USA